Social (un)distancing: Teammate interactions, athletic identity, and mental health of student-athletes during the COVID-19 pandemic - Graupensperger, S.; Benson, A. J.; Kilmer, J. R.; Evans, M. B. (Journal of Adolescent Health, 2020)
Purpose: Physical distancing measures to combat the spread of the novel coronavirus have presented challenges for the mental health and well-being of college students. As campus activities ceased, student-athletes abruptly became isolated from teammates and were no longer able to participate in sport activities that are often central to their identity as an athlete. However, student-athletes who have supportive social connections with teammates during this pandemic may maintain their athletic identity to a greater extent and report better mental health. The present study examined how student-athletes` mental health was associated with teammate social support, connectedness, and changes to athletic identity from before to during COVID-19. Method: A sample of 234 student-athletes completed surveys before COVID-19 physical distancing (February 2020), with 135 (63% female) participating in a follow-up in the month following school closures (April 2020). Path models estimated the effects of teammate social support and connectedness (during COVID-19), as well as changes in athletic identity on indices of mental health. Results: Considering all path models tested, student-athletes who received more social support and reported more connectedness with teammates reported less dissolution of their athletic identity and—in most models—reported better mental health and well-being. Indirect effects indicated that student-athletes` change in athletic identity mediated the effects of teammate social support on psychological well-being and depression symptoms. Conclusions: In addition to advancing theory on how small groups relate to mental health, these findings demonstrate the value in remaining socially connected with peers and maintaining role identities during the COVID-19 pandemic.